2011
DOI: 10.1185/03007995.2011.568059
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of sitagliptin monotherapy in elderly patients with type 2 diabetes: a randomized, double-blind, placebo-controlled trial

Abstract: In this study, sitagliptin treatment significantly and rapidly improved glycemic measures and was well tolerated in patients aged ≥ 65 years with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 25 publications
6
73
1
3
Order By: Relevance
“…These findings were echoed in a review of the World Health Organization Clinical Trials Registry Platform where of the 440 studies examining type 2 diabetes therapies, nearly 66% excluded individuals based on an arbitrary upper age limit (3). This worrisome evidence gap has led to the question of whether it is sound clinical practice to extrapolate the findings derived from type 2 diabetes (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Two meta-analyses suggested that the DPP-4 inhibitors are associated with reduced CV risk (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were echoed in a review of the World Health Organization Clinical Trials Registry Platform where of the 440 studies examining type 2 diabetes therapies, nearly 66% excluded individuals based on an arbitrary upper age limit (3). This worrisome evidence gap has led to the question of whether it is sound clinical practice to extrapolate the findings derived from type 2 diabetes (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Two meta-analyses suggested that the DPP-4 inhibitors are associated with reduced CV risk (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses suggested that the DPP-4 inhibitors are associated with reduced CV risk (23,24). Importantly, however, these data were obtained predominantly from relatively small and/or short-term investigations (18,19,30), systematic reviews (21,28,29), and pooled analyses (20,22,(25)(26)(27)31,32) in by-and-large younger and healthier study participants with very limited, and generally unadjudicated, CV safety information.…”
Section: Discussionmentioning
confidence: 99%
“…In this placebocontrolled, 24-week study, sitagliptin treatment (100 or 50 mg, depending on renal function) significantly and rapidly improved glycaemic measures (reductions in HbA 1c from 0.5% to 1.6%, depending on baseline levels), and was well tolerated with no adverse episodes of hypoglycaemia in patients aged > 65 years with T2DM without severe RI [96].…”
Section: Elderly Patientsmentioning
confidence: 91%
“…Due to their favorable safety profile, especially in terms of reduced hypoglycemia, DPP-4 inhibitors are pro bably the only oral glucose-lowering agents for which some evidence from dedicated randomized clinical trials in patients aged ≥65 years and/or with moderate to severe renal impairment has been published over the last few years. 3,19,[32][33][34][35][36][37][38][39][40] One of these studies, a randomized, placebocontrolled trial in 133 patients with type 2 diabetes (HbA1c 7%-10%) and severe renal impairment (eGFR <30 mL/min per 1.73 m 2 ) showed that adding linagliptin (5 mg/day) to existing background therapy resulted in a significantly greater reduction of HbA1c at 12 weeks 36 which was maintained at 1 year (P<0.0001 vs baseline). In linagliptin-treated patients the incidence of adverse events and severe hypoglycemia was similar to the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…2,14,15,17 Dipeptidyl peptidase-4 (DPP-4) inhibitors have emerged in recent years as a class of oral glucose-lowering agents suitable for elderly patients, since they are generally well tolerated, have a low risk for hypoglycemia and lack significant drug interactions. 2,14,18,19 inhibitors stimulate the release of insulin in a glucose-dependent manner by counteracting the inactivation of incretins. 18,20 Linagliptin is a potent, long-acting DPP-4 inhibitor approved for the treatment of type 2 diabetes mellitus as monotherapy or as combination therapy with other oral antidiabetic agents or insulin.…”
Section: Introductionmentioning
confidence: 99%